2018
DOI: 10.21767/2574-2817.100007
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Lumbotomy Approach for Pediatric Dismembered Pyeloplasty

Abstract: Aim: Recently, the posterior lumbotomy approach has become widely popular for pediatric pyeloplasty. The current study reassesses the approach for pediatric dismembered pyeloplasty considering its advantages and limitations. Materials and methods:We conducted a prospective study with 84 cases of hydronephrosis due to ureteropelvic junction obstruction, over a period of five years. We excluded the cases of hydronephrosis in ectopic or rotated kidney and cases of revision surgery (redo pyeloplasty). All patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The average hospital stay duration was 3.9 days, and interestingly analgesia requirements were much lower, with only oral paracetamol given when required. 14 We report a lower average operative time than the literature. The credit goes to the age range at which our patients operated, especially since the back muscles are easier to split, and fewer layers require opening.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The average hospital stay duration was 3.9 days, and interestingly analgesia requirements were much lower, with only oral paracetamol given when required. 14 We report a lower average operative time than the literature. The credit goes to the age range at which our patients operated, especially since the back muscles are easier to split, and fewer layers require opening.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast, many studies report an average range of 1 month-12 year [9][10][11][12][13] with an antenatal diagnosis of as low as 0.09%. 14 Currently, there are two widely used measurement systems: anteroposterior diameter of the renal pelvis (APDRP) and the society of fetal urology (SFU) hydronephrosis grading system. 15,16 Although recent studies call for the improvement of these systems, we found the latter system to be suitable in predicting prognosis and follow up, with most showing significant improvement on follow up (z = -5.654, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pyeloplasty can be performed through the dorsal lumbotomy approach with an incision below the 12th rib (Mikhail & Hall, 2020;Peters, 2015). Although some studies have recommended mobilization of the 12th rib by dividing the costovertebral ligaments to increase exposure (Gonzalez & Aliabadi, 1987;Orland et al, 1987), most have reported that the operation does not require this technique in the pediatric population (Bajpai et al, 2004;Gonzalez & Aliabadi, 1987;Gupta & Sharma, 2011;Halder et al, 2017). In our study, a minority of right kidneys showed relationships above the 12th rib in all age groups, and a minority of left kidneys in most age groups.…”
Section: Discussionmentioning
confidence: 99%